A universal pharmacy: Possible self-medication using tree balsam by multiple Atlantic Forest mammals - Kaisin, Olivier [UNESP]; Rocha, Fernanda Corrêa; Amaral, Rodrigo Gonçalves [UNESP]; Bufalo, Felipe [UNESP]; Sabino, Gabriel Pavan [UNESP]; Culot, Laurence [UNESP] (Wiley, 2022)
We present camera trap evidence of 10 Atlantic Forest mammals fur-rubbing, licking, or biting balsam from cabreúvas (Myroxylon peruiferum, Fabaceae), native trees used in traditional medicine for their prophylactic and therapeutic virtues. Given the antiparasitic properties of cabreúvas, mammals may be using the balsam as topical self-medication to repel ectoparasites. Abstract in Portuguese is available with online material.
Keywords: cabreúva; camera trap; fur-rubbing; medicinal plants; Myroxylon peruiferum; zoopharmacognosy